Efficacy and safety of ertugliflozin in East/Southeast Asian patients with type 2 diabetes mellitus. Issue 4 (3rd January 2020) - Liu, Jie; Patel, Shrita; Cater, Nilo B.; Wu, Larry; Huyck, Susan; Terra, Steven G.; Hickman, Anne; Darekar, Amanda; Pong, Annpey; Gantz, Ira
ABSTRACT: Aim: Post‐hoc analysis of the efficacy and safety of ertugliflozin in East/Southeast (E/SE) Asian patients with type 2 diabetes mellitus (T2DM). Materials and Methods: Efficacy evaluations used data from randomized, double‐blind, phase 3 studies: a pool of two 26‐week placebo‐controlled studies and one 52‐week active‐comparator (glimepiride) study. Least squares mean change from baseline was calculated for HbA1c, fasting plasma glucose (FPG), body weight (BW) and systolic blood pressure (SBP). Safety evaluation included overall and prespecified adverse events based on pooled data (broad pool) from seven phase 3 studies (including studies in the efficacy analysis). Results: Among 161 E/SE Asian patients in the placebo pool (ertugliflozin, n = 106), ertugliflozin reduced HbA1c, FPG, BW and SBP from baseline at week 26. The placebo‐adjusted changes from baseline for ertugliflozin 5 and 15 mg were: HbA1c, −0.9% and −1.0%; BW, −2.1 and −1.9 kg; and SBP, –3.3 and −3.5 mmHg, respectively. Among 174 E/SE Asian patients in the active‐comparator study (ertugliflozin, n = 118), HbA1c changes from baseline at week 52 were −0.6%, −0.6% and −0.7% for ertugliflozin 5 mg, 15 mg and glimepiride, respectively. Ertugliflozin 5 and 15 mg reduced BW from baseline by −4.3 and −4.1 kg, respectively, and SBP by −7.4 and −9.3 mmHg, respectively, compared with glimepiride. Safety findings were generally consistent with overall ertugliflozin safety data published to date. Conclusions: Treatment with ertugliflozin was associated with reductions in HbA1c, FPG, BW and SBP, and was generally well tolerated in E/SE Asian patients with T2DM. ClinicalTrials.gov identifier: NCT01986855, NCT01999218, NCT01958671, NCT02099110, NCT02036515, NCT02033889, NCT02226003.